Nasi ambeng: the irony of Malaysian Javanese comfort food that's a pain to prep / Nadia Liana Mohd Karim ... [et al.] - Mohd Karim, Nadia Liana; Abd Hadi, Arnieyantie; Salmi, Noor Saliza; Ab Rashid, Putri Dahlia (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Two things you'll miss once you move out of your hometown: your parents and your comfort food. Period. At your new place, you can't recreate your parents, obviously. But food, that's replicable. Even as our palates have broadened, we continue to gravitate towards local delicacies. Comfort foods as we call them, are those foods that could nourish you not just physically, but more importantly...sentimentally. You would think I'd say 'spiritually' just for the jingle of the phrase, but we know it's beyond that. Comfort foods bring back memories and all the good feelings you had as a child, and if you are still in the same country, recreating comfort food should be easy. Nasi ambeng is one of the items on my long list of Southern-flair comfort foods.